RUANG BUDAYA GLODOK, ANTARA BERHUNI, BUDAYA DAN ADAPTASI - Kenny Kenny; Mieke Choandi (Jurusan Arsitektur dan Perencanaan, 2021)
Nowadays, culture is a lifestyle that develops in a community group and is passed down from generation to generation. In addition if this culture is already attached to an area, for example Chinatown. Where these popilation and lifestyle are very thick with Chinese culture.As an example of china town that we know, Glodok, which is very attached to Chinese culture, can be seen from the old Chinese building style, the lifestyle of the people that has majority whom work as traders, and many cultural or traditional events that are held in Glodok. But in the mean time these Chinese culture starts to fading even disappearing from it, and this issue is causing the people that lived here with the inherent culture facing a crisis of regional identity and cultural identity that should be the character of Chinatown itself.This proposed project appears in the form of a Cultural Space that can accommodate traditional and cultural activities with the ultimate goal of awakening and preserving Chinese culture for the local community even on a city scale. In addition to generating and preserving, this project aims to provide a new spatial experience as the new face of Chinatown and as a breakthrough Nodes in the region. Keywords: Chinatown; Chinese; Cultural Space; Nodes; Westernization ABSTRAKDalam kehidupan sehari-hari budaya merupakan suatu gaya hidup yang berkembang dalam suatu kelompok masyarakat dan diwariskan secara turun menurun. Ditambah lagi jika budaya tersebut sudah melekat dengan sebuah kawasan contohnya, Pecinan dimana penduduk dan gaya hidupnya sangat kental dengan budaya China. Salah satu contoh Pecinan yang kita kenal merupakan Glodok. Kawasan Glodok yang sangat kental dengan budaya China dapat dilihat dari gaya bangunan, pola hidup masyarakatnya yang mayoritas bermata pencaharian sebagai pedagang, dan banyaknya acara kebudayaan atau tradisi yang dilakukan di kawasan Glodok.Namun seiring dengan berjalannya waktu budaya tersebut semakin memudar bahkan hilang yang menimbulkan masyarakat etnis Tionghoa yang pernah hidup di dalam kekentalan budaya disini menghadapi krisis identitas Kawasan dan identitas budaya yang seharusnya menjadi ciri khas pecinan sendiri.Muncullah usulan proyek berupa cultural space yang dapat mewadahi aktivitas tradisi dan kebudayaan dengan tujuan akhir membangkitkan dan melestarikan budaya China bagi masyarakat setempat bahkan dalam skala kota.Selain untuk membangkitkan dan melestarikan, proyek ini memiliki tujuan untuk memberi pengalaman spasial yang baru sebagai wajah Pecinan yang baru dan sebagai terobosan Nodes baru di kawasan ini.